Evaluation of Endotracheal Tube Cuff Pressure and the Use of Three Cuff Inflation Syringe Devices in Dogs - Hung, Wan-Chu; Ko, Jeff C.; Weil, Ann B.; Weng, Hsin-Yi (Frontiers in Veterinary Science, 2020)
Over-inflation of an endotracheal tube (ETT) cuff may lead to tracheal mucosal irritation, tracheal wall ischemia or necrosis, whereas under-inflation increases the risk of pulmonary aspiration as well as leaking anesthetic gas and polluting the environment. The objectives of this two-phase study were to 1) identify the incidence of improper ETT cuff inflation (both over- and under-inflation) using the minimum occlusive volume (MOV) technique coupled with a regular injectable syringe in the anesthetized dogs, and 2) evaluate the performance of two commercially available inflation syringe devices (Tru-Cuff and AG Cuffill®) with the regular injectable syringe in inflating the ETT cuff to a recommended safe cuff pressure range (20 to 30 cmH2O). Dogs undergoing general anesthesia at Purdue Veterinary Medicine Teaching Hospital (PVMTH) were included. The ETT cuff pressure was assessed with an aneroid manometer after the syringe inflation. The results of the first objective showed that a total of 80 dogs enrolled and that 50 of these 80 dogs required ETT cuff inflation. Among the 50 dogs, only 14% had proper ETT cuff inflation; 76% of the ETT cuffs were over-inflated and 10% were under-inflated. Ninety dogs were enrolled for the second objective study and they were randomly and equally assigned to the three syringe device treatment groups. The results showed that 80% of the ETT cuffs were over-inflated in the regular injectable syringe treatment group, whereas only 6.7% and 3.3% ETT cuffs were over-inflated with the Tru-Cuff and AG Cuffill® syringe treatment groups, respectively. The AG Cuffill® syringe treatment group had a significantly (p< 0.05) higher percentage of proper inflated ETT cuffs (86.7%) compared to the other two groups (regular injectable syringe [3.3%]; Tru-Cuff [50%] syringe). We concluded that there was a high incidence of improper ETT cuff inflation when using MOV technique coupled with a regular injectable syringe. The use of an AG Cuffill® syringe significantly reduced improper ETT cuff inflation.